Cursing the blessings? Natural resource abundance, institutions, and economic growth - Christa N. Brunnschweiler (ETH Zurich, CER-ETH - Center of Economic Research, 2006)
Since Sachs and Warner's (1995a) contribution, there has been a lively debate on the so-called natural resource curse. This paper re-examines the effects of natural resource abundance on economic growth using new measures of resource endowment and considering the role of institutional quality. We find a positive direct empirical relationship between natural resource abundance and economic growth. In both OLS and 2SLS re- gressions, the positive resource effects are particularly strong for subsoil wealth. Our results also show no evidence of negative indirect effects of natural resources through the institutional channel.
Keywords: O11; O13; Q0; 330; Natural resources; resource curse; economic growth; institutional quality; Natürliche Ressourcen; Wirtschaftswachstum; Schätzung; Kleinste-Quadrate-Methode